Supporting the Recovery of Travel Agencies in Bali through Softloan - Meinarni, Ni Putu Suci; Thalib, Emmy Febriani; Manurung, Evelyn Angelita Pinondang; Wijaya, Bagus Kusuma; Winatha, Komang Redy (Jurnal Bali Membangun Bali, 2023)
Purpose: The aim of this paper is to address the challenges faced by Travel Agencies in Indonesia due to the significant decrease in the tourism sector caused by the Covid-19 pandemic. The paper aims to find a solution for Travel Agencies, particularly in terms of capital. Research methods: The paper utilizes a mixed-method research approach. The descriptive analysis method with a qualitative approach is employed to describe and summarize the current situation and conditions that Travel Agencies are facing. It also involves analyzing regulations related to the industry. Additionally, a quantitative method is used to gather information from travel agency business actors through the completion of a questionnaire. Results and discussion: The Covid-19 pandemic has led to a significant decrease in the tourism sector in Indonesia, particularly affecting Travel Agencies, which face challenges due to suspended operational activities and a reliance on tourist visit transactions. Implication: To address the capital needs of Travel Agencies and support their recovery, utilizing the government's national economic recovery program, including options like interest subsidies and credit restructuring at banks, is crucial.